1989
DOI: 10.1002/jor.1100070516
|View full text |Cite
|
Sign up to set email alerts
|

Transverse stability of the carpus. An analytical study

Abstract: The stabilizing structures of the transverse carpal arch were studied utilizing an analytical model based on a rigid body spring model theory. This method was used to calculate the relative motion between carpal bones, the distribution of compressive forces in the intercarpal joints, and the tensions in the ligaments under simulated dorsopalmar compression. The contribution of each ligament against the effect of compression was determined by removing ligaments from the model. A multivariate analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…25 Garcia-Elias et al also theoretically and experimentally investigated the biomechanical importance of these ligaments. 26,27 They simulated compression-type injuries to the carpus, whereas our simulation was conducted assuming injuries in the extended position. Although conditions differed, both studies confirmed the importance of palmar intercarpal ligaments for the carpal arch.…”
Section: Discussionmentioning
confidence: 99%
“…25 Garcia-Elias et al also theoretically and experimentally investigated the biomechanical importance of these ligaments. 26,27 They simulated compression-type injuries to the carpus, whereas our simulation was conducted assuming injuries in the extended position. Although conditions differed, both studies confirmed the importance of palmar intercarpal ligaments for the carpal arch.…”
Section: Discussionmentioning
confidence: 99%
“…These treatment and intervention strategies mainly rely on the understanding of the mechanical properties of carpal tunnel. Few studies have been designed to address the basic biomechanics of the carpal tunnel (Garcia-Elias et al, 1989a, Garcia-Elias et al, 1989b, Fuss and Wagner, 1996). The understanding of carpal tunnel mechanics helps to improve the existing strategies and to develop alternatives for the treatment of carpal tunnel syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Division of the transverse carpal ligament changes the anatomy by increasing the carpal arch width, increasing the carpal tunnel volume, and changing the tendon mechanics. 6 Without the transverse ligament retaining the flexor tendons, the tendons may displace volarly.…”
Section: Discussionmentioning
confidence: 99%